2018
DOI: 10.1001/jamaneurol.2017.4198
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Top 20 Alzheimer Disease Risk Variants With Brain Amyloidosis

Abstract: IMPORTANCE Late-onset Alzheimer disease (AD) is highly heritable. Genome-wide association studies have identified more than 20 AD risk genes. The precise mechanism through which many of these genes are associated with AD remains unknown. OBJECTIVE To investigate the association of the top 20 AD risk variants with brain amyloidosis. DESIGN, SETTING, AND PARTICIPANTS This study analyzed the genetic and florbetapir F 18 data from 322 cognitively normal control individuals, 496 individuals with mild cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 98 publications
7
96
1
Order By: Relevance
“…APOE was also the top-associated region in the ADNI dataset (Suppl. Table 2), as previously described [26]. Interestingly, in analyses comparing MCI vs. controls, the APOE region did not emerge as strongly associated (i.e.…”
Section: Gwas On Diagnostic Outcomessupporting
confidence: 75%
“…APOE was also the top-associated region in the ADNI dataset (Suppl. Table 2), as previously described [26]. Interestingly, in analyses comparing MCI vs. controls, the APOE region did not emerge as strongly associated (i.e.…”
Section: Gwas On Diagnostic Outcomessupporting
confidence: 75%
“…The NINCDS-ADRDA criteria are symptom-and individual doctor-based diagnosis, and therefore, may yield inconsistencies between different datasets. Using a single nucleotide polymorphism dataset in ADNI, Apostolova et al 74 curated seven variants using brain amyloidosis as a dependent variable, while only one variant (FERMT2) was found using the AD stage determined by the NINCDS-ADRDA as a dependent variable. In addition, Edmonds et al 75 suggested that some MCI samples diagnosed by the NINCDS-ADRDA are false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, genetic meta-analysis identified another risk factor involved in cholesterol homeostasis: the ATP binding cassette ABC transporter 7 (ABCA7) gene. Intriguingly, ABCA7 has one of the strongest association with amyloid deposition, exceeded only by APOE e4 (Apostolova et al, 2018).…”
Section: Genetic Risk Factors For Ad Involved In Cholesterol Homeostasismentioning
confidence: 99%